Effects of a Fact Sheet on beliefs about the harmfulness of alternative nicotine delivery systems compared with cigarettes - Borland Ron; Li Lin; Cummings K; O'Connor Richard; Mortimer Kevin; Wikmans Tom; Ramstrom Lars; King Bill; McNeill Ann (BMC, 2012)
Abstract Background This study explored the value of providing information in a Fact Sheet to correct misperceptions about the relative harmfulness of nicotine replacement products (NRT) and smokeless tobacco (ST), when compared to cigarette smoking. Methods Four convenience samples from different countries (Australia, UK, Sweden and USA) were surveyed concerning their beliefs about the relative harmfulness of smokeless tobacco and NRT. Study participants were given the Fact Sheet that explained that nicotine, as used by consumers, is not particularly harmful and explained why. They were resurveyed one week later regarding their beliefs about the relative harmfulness of smokeless tobacco and NRT and future intentions to use the products. Results In all four samples knowledge increased by similar amounts and beliefs regarding the lower harmfulness of smokeless tobacco increased. However, misconceptions remained common and responses to belief measures were not always consistent. Likelihood of use of ST increased in all four samples after exposure to the Fact Sheet, but interest in NRT use only increased in the US sample. Conclusions A Fact Sheet such as this one can help address misconceptions about NRT and smokeless tobacco, at least in the short term. However, as is true of most educational interventions, exposure to a single educational session is not sufficient to overcome misperceptions that smokers have about the relative harmfulness of oral versus combustible forms of nicotine delivery.